Реєстр сучасного загальномовного словника і лексикографічний стандарт - Козирєва, З. (Лексикографічний бюлетень, 2015)
In article the basic tendencies and directions of development of a modern Ukrainian lexicon are defi ned. Th e author pays att ention to some aspects of it process in sphere of word usage and word-formation. Key words: Lexicon, replenishment and lexicon reduction, doublets, loans speaking another language.